2009
DOI: 10.1029/2009gc002625
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional dynamics of hydrous thermal‐chemical plumes in oceanic subduction zones

Abstract: [1] Hydration and partial melting along subducting slabs can trigger Rayleigh-Taylor-like instabilities. We use 3-D petrological-thermomechanical numerical simulations to investigate small-scale convection and hydrous, partially molten, cold plumes formed in the mantle wedge in response to slab dehydration. The simulations were carried out with the I3ELVIS code, which is based on a multigrid approach combined with marker-in-cell methods and conservative finite difference schemes. Our numerical simulations show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
103
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(111 citation statements)
references
References 95 publications
(132 reference statements)
6
103
1
1
Order By: Relevance
“…These changes are closely related to the mantle structure, including that of: (1) the upwellingsubsidence of the asthenosphere during the backarc basin period; and (2) the mantle wedge corner flow in the island-arc period. Such a temporal development of the mantle has been investigated by EVOLUTION OF LATE CENOZOIC MAGMATISM, NE JAPAN ARCseveral geodynamic models (Honda & Yoshida 2005a, b;Honda et al 2007;Zhu et al 2009). …”
Section: Mantle Dynamics and Arc Magmatismmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes are closely related to the mantle structure, including that of: (1) the upwellingsubsidence of the asthenosphere during the backarc basin period; and (2) the mantle wedge corner flow in the island-arc period. Such a temporal development of the mantle has been investigated by EVOLUTION OF LATE CENOZOIC MAGMATISM, NE JAPAN ARCseveral geodynamic models (Honda & Yoshida 2005a, b;Honda et al 2007;Zhu et al 2009). …”
Section: Mantle Dynamics and Arc Magmatismmentioning
confidence: 99%
“…Alternatively, Zhu et al (2009) simulated the 3D dynamics of hydrous thermo-chemical plumes in the oceanic subduction zones, and computed the spatial and temporal patterns of melt generation intensity above the slab, then compared results with data from the NE Japan arc. This suggested that the clustering of volcanic activity could potentially be related to the activity of thermal-chemical plumes in the mantle wedge.…”
Section: Mantle Dynamics and Arc Magmatismmentioning
confidence: 99%
“…2e,f). The characteristics and 2D and 3D dynamics of this kind of plume are studied in detail in Gerya and Yuen (2003b) and Zhu et al (2009). As continental subduction continues, partially molten rocks accumulated in the subduction channel extrude upward to the crustal depths (Fig.…”
Section: Model Results 41 Reference Modelmentioning
confidence: 99%
“…The model results help to explain the fundamental features such as the one-sided subduction and the stress regimes of continental collision [e.g., Gerya et al, 2008;Faccenda et al, 2009]. They also demonstrate that small-scale features and complicated dynamic processes due to the thermochemical convection may be present in the mantle wedge and account for the variations in crustal growth rate and arc compositions [e.g., Arcay et al, 2007;Gorczyk et al, 2007;Nikolaeva et al, 2008;Zhu et al, 2009]. However, these models only apply to the back-arc basins where the spreading center initiates in the forearc region because of the weakening caused by either serpentinization [e.g., Nikolaeva et al, 2008;Gerya et al, 2008;Faccenda et al, 2009;Zhu et al, 2009] or the presence of broad, welldeveloped accretionary wedge system [e.g., Gorczyk et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…They also demonstrate that small-scale features and complicated dynamic processes due to the thermochemical convection may be present in the mantle wedge and account for the variations in crustal growth rate and arc compositions [e.g., Arcay et al, 2007;Gorczyk et al, 2007;Nikolaeva et al, 2008;Zhu et al, 2009]. However, these models only apply to the back-arc basins where the spreading center initiates in the forearc region because of the weakening caused by either serpentinization [e.g., Nikolaeva et al, 2008;Gerya et al, 2008;Faccenda et al, 2009;Zhu et al, 2009] or the presence of broad, welldeveloped accretionary wedge system [e.g., Gorczyk et al, 2007]. The episodicity of the back-arc tectonics have also been studied with three-dimensional numerical models [e. g., Clark et al, 2008] in which spreading is achieved by prescribing a weak zone for the arc with a viscous overriding lithosphere.…”
Section: Introductionmentioning
confidence: 99%